Comparison of Plasma Carcinoembryonic Antigen Levels to Clinicopathological Features of Colorectal Cancer in Ugandan Patients - Wismayer, Richard; Kiwanuka, Julius; Wabinga, Henry; Odida, Michael (Achievements and Challenges of Medicine and Medical Science Vol. 2, 2024)
Introduction: Carcinoembryonic antigen (CEA) is the most widely used tumour marker in Uganda and globally. In 1965 Gold and Freedman observed that the CEA molecular marker is present in fetal gut tissues and in tumours of the gastrointestinal tract. Factors which have been found to affect plasma CEA levels include tumour grade, stage, location of the tumour, ploidy status of the tumour, absence or presence of bowel obstruction and liver status. This study aimed to investigate the preoperative plasma CEA level and compare it to clinicopathological features in Ugandan colorectal cancer patients. Methodology: A prospective observational study was used on 119 recruited colorectal cancer (CRC) participants. Using a standard pretested Data Extraction Form, data for all the participants was extracted from the clinical patients’ files in the respective hospitals. A 10 ml blood sample was taken preoperatively from all the participants to obtain the CEA level in ng/ml. ANOVA and student’s t-test were used to compare mean CEA levels. Pearson chi-square tests were used to determine any association between CEA levels and clinicopathological variables. A p-value of \(\le\)0.05 was statistically significant. Results: The mean age of all the participants was 55.9(+/-15.3) years whilst the mean CEA level was 23.6(+/-8.51) ng/ml. There was no significant difference between preoperative plasma CEA and topography (p=0.775), stage (p=0.813), grade (p=0.505) and histopathological subtype (p=0.940). Conclusions: There was no difference in preoperative plasma CEA levels based on histopathological grade, stage, topography and histopathological subtype of CRC in Ugandan patients. Therefore, the plasma CEA levels in Ugandan patients did not increase with increasing histopathological grade and stage and were not affected by the location and histopathological subtype of the colorectal tumour.